Muscle MCT4 Content Is Correlated with the Lactate Removal Ability during Recovery Following All-Out Supramaximal Exercise in Highly-Trained Rowers - Maciejewski, Hugo; Bourdin, Muriel; Féasson, Léonard; Dubouchaud, Hervé; Denis, Christian; Freund, Hubert; Messonnier, Laurent A. (Frontiers in Physiology, 2016)
The purpose of this study was to test if the lactate exchange (γ1) and removal (γ2) abilities during recovery following short all-out supramaximal exercise correlate with the muscle content of MCT1 and MCT4, the two isoforms of the monocarboxylate transporters family involved in lactate and H+ co-transport in skeletal muscle. Eighteen lightweight rowers completed a 3-min all-out exercise on rowing ergometer. Blood lactate samples were collected during the subsequent passive recovery to assess an individual blood lactate curve (IBLC). IBLC were fitted to the bi-exponential time function: La(t) = [La](0) + A1(1 – e– γ1t) + A2(1 – e– γ2t) where [La](0) is the blood lactate concentration at exercise completion and the velocity constants γ1 and γ2 denote the lactate exchange and removal abilities, respectively. An application of the bi-compartmental model of lactate distribution space allowed estimation of the lactate removal rate at exercise completion [LRR(0)]. Biopsy of the right vastus lateralis was taken at rest to measure muscle MCT1 and MCT4 content. Fiber type distribution, activity of key enzymes and capillary density (CD) were also assessed. γ1 was correlated with La(0) (r = –0.54, P < 0.05) but not with MCT1, MCT4 or CD. γ2 and LRR(0) were correlated with MCT4 (r = 0.63, P < 0.01 and r = 0.73, P < 0.001, respectively) but not with MCT1 or cytochrome c oxidase activity. These findings suggest that the lactate exchange ability is highly dependent on the milieu so that the importance of the muscle MCT1 and MCT4 content in γ1 was hidden in the present study. Our results also suggest that during recovery following all-out supramaximal exercise in well-trained rowers, MCT4 might play a significant role in the distribution and delivery of lactate for its subsequent removal